Carving Metacognition at its Joints: Protracted Development of Component Processes - O’Leary, Allison (Child Dev, 2016)
Two experiments investigated the development of metacognitive monitoring and control and conditions under which children engage these processes. In Experiment 1, 5-year-olds (N = 30) and 7-year-olds (N = 30), unlike adults (N = 30), showed little evidence of either monitoring or control. In Experiment 2, 5-year-olds (N = 90) were given performance feedback (aimed at improving monitoring), instruction to follow a particular strategy (aimed at improving control), or both. Across conditions, feedback improved children’s monitoring, and instruction improved both monitoring and control. Thus, children’s poor metacognitive performance likely reflects a difficulty engaging the component processes spontaneously, rather than a lack of metacognitive ability. These findings also suggest that the component processes are distinct, with both undergoing protracted development.